2014
DOI: 10.1074/jbc.m113.535245
|View full text |Cite
|
Sign up to set email alerts
|

Gene Trap Mice Reveal an Essential Function of Dual Specificity Phosphatase Dusp16/MKP-7 in Perinatal Survival and Regulation of Toll-like Receptor (TLR)-induced Cytokine Production

Abstract: Background: Dual specificity phosphatases (DUSPs) have emerged as important regulators of MAPK signaling and responses, including immune responses. Results: Dusp16-deficient gene trap mice were generated and show a phenotype of perinatal lethality and altered cytokine responses to TLR stimulation. Conclusion: Dusp16 has non-redundant functions in the innate immune system. Significance: This is the first description of a mouse model of Dusp16 deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…The results revealed embryonic lethality of Mkp7 2/2 mice with the majority of the KO mice dying between embryonic days 15.5 and 17.5 (Supplemental Fig. 2C), demonstrating that MKP7 is required for normal embryonic development in mice, which is similar to a recently published study (12).…”
Section: Mkp7 Deficiency Results In Embryonic Lethalitysupporting
confidence: 77%
See 2 more Smart Citations
“…The results revealed embryonic lethality of Mkp7 2/2 mice with the majority of the KO mice dying between embryonic days 15.5 and 17.5 (Supplemental Fig. 2C), demonstrating that MKP7 is required for normal embryonic development in mice, which is similar to a recently published study (12).…”
Section: Mkp7 Deficiency Results In Embryonic Lethalitysupporting
confidence: 77%
“…The expression of Th17 lineage-specific genes including IL-17A, IL-17F, IL-21 and IL-22, and RORgt, the transcription factor essential for Th17 differentiation (12,16), were determined by quantitative RT-PCR. We found that the expression of Th17 lineage-specific genes and transcription factor was impaired in MKP7 KO Th17 cells compared with WT cells (Fig.…”
Section: Mkp7 Is Required For Th17 Differentiation and Effector Functmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Dusp family members are highly inducible by MAPKactivating stimuli and act as negative feedback regulators. Examples with an established function in the immune system are Dusp1/MKP-1 (10-13), Dusp2/PAC1 (14), Dusp10/MKP-5 (15), and Dusp16/MKP-7 (16,17). Investigations in the respective knockout mice have shown that a lack of these inducible Dusp phosphatases leads to alterations in the patterns of cytokines produced via the effects of dysregulated MAPK activation (for review, see Refs.…”
Section: N Innate Immune Cells Recognition Of Microbial Ligands Bymentioning
confidence: 99%
“…ERK, JNK, p38) via dephosphorylation of phosphotyrosine and phosphothreonine residues, and thus play a key role in inflammation mediated diseases. Indeed various MKPs including MKP-1, MKP-5, MKP-7, MKP-x (DUSP22) and DUSP5 have been shown to be important in regulating immune responses123456. For example, MKP-1 negatively regulates the production of inflammatory cytokines TNF-α, IL-6 and IL-1β, and the anti-inflammatory IL-10789, as well as chemokines and other inflammatory mediators10111213.…”
mentioning
confidence: 99%